Is Social Categorization Spatially Organized in a “Mental Line”? Empirical Evidences for Spatial Bias in Intergroup Differentiation - Presaghi, Fabio; Rullo, Marika (Frontiers in Psychology, 2018)
Social categorization is the differentiation between the self and others and between one’s own group and other groups and it is such a natural and spontaneous process that often we are not aware of it. The way in which the brain organizes social categorization remains an unresolved issue. We present three experiments investigating the hypothesis that social categories are mentally ordered from left to right on an ingroup–outgroup continuum when membership is salient. To substantiate our hypothesis, we consider empirical evidence from two areas of psychology: research on differences in processing of ingroups and outgroups and research on the effects of spatial biases on processing of quantitative information (e.g., time; numbers) which appears to be arranged from left to right on a small–large continuum, an effect known as the spatial-numerical association of response codes (SNARC). In Experiments 1 and 2 we tested the hypothesis that when membership of a social category is activated, people implicitly locate ingroup categories to the left of a mental line whereas outgroup categories are located on the far right of the same mental line. This spatial organization persists even when stimuli are presented on one of the two sides of the screen and their (explicit) position is spatially incompatible with the implicit mental spatial organization of social categories (Experiment 3). Overall the results indicate that ingroups and outgroups are processed differently. The results are discussed with respect to social categorization theory, spatial agency bias, i.e., the effect observed in Western cultures whereby the agent of an action is mentally represented on the left and the recipient on the right, and the SNARC effect.